Protective Ventilation Improves Gas Exchange, Reduces Incidence of Atelectases, and Affects Metabolic Response in Major Pancreatoduodenal Surgery - Kuzkov, Vsevolod V.; Rodionova, Ludmila N.; Ilyina, Yana Y.; Ushakov, Aleksey A.; Sokolova, Maria M.; Fot, Eugenia V.; Duberman, Boris L.; Kirov, Mikhail Y. (Frontiers in Medicine, 2016)
Background Protective perioperative ventilation has been shown to improve outcomes and reduce the incidence of postoperative pulmonary complications. The goal of this study was to assess the effects of ventilation with low tidal volume (VT) either alone or in a combination with moderate permissive hypercapnia in major pancreatoduodenal interventions. Materials and methods Sixty adult patients scheduled for elective pancreatoduodenal surgery with duration >2 h were enrolled into a prospective single-center study. All patients were randomized to three groups receiving high VT [10 mL/kg of predicted body weight (PBW), the HVT group, n = 20], low VT (6 mL/kg PBW, the LVT group, n = 20), and low VT combined with a moderate hypercapnia and hypercapnic acidosis (6 mL/kg PBW, PaCO2 45–60 mm Hg, the LVT + HC group, n = 20). Cardiopulmonary parameters and the incidence of complications were registered during surgery and postoperatively. Results and discussion The values of VT were 610 (563–712), 370 (321–400), and 340 (312–430) mL/kg for the HVT, the LVT, and the LVT + HC groups, respectively (p < 0.001). Compared to the HVT group, PaO2/FiO2 ratio was increased in the LVT group by 15%: 333 (301–381) vs. 382 (349–423) mm Hg at 24 h postoperatively (p < 0.05). The HVT group had significantly higher incidence of atelectases (n = 6), despite lower incidence of smoking compared with the LVT (n = 1) group (p = 0.017) and demonstrated longer length of hospital stay. The patients of the LVT + HC group had lower arterial lactate and bicarbonate excess values by the end of surgery. Conclusion In major pancreatoduodenal interventions, preventively protective VT improves postoperative oxygenation, reduces the incidence of atelectases, and shortens length of hospital stay. The combination of low VT and permissive hypercapnia results in hypercapnic acidosis decreasing the lactate concentration but adding no additional benefits and warrants further investigations.